Understanding mathematics for aircraft navigation - Wolper, James S. (New York : McGraw-Hill, 2001)
"Navigating is easier and safer when you truly understand how it works. This in-the-cockpit guide helps you build that base of understanding. Written by flight instructor/mathematician/computer expert/teacher James S. Wolper, Understanding Mathematics for Aircraft Navigation helps you handle - and grasp - every aspect of getting from here to there, determining where you are now, taking full advantage of today's sophisticated navigation equipment, and even using ancient celestial methods in an emergency."--Jacket.
1. The shape of the Earth -- 2. Vectors and spheres -- 3. Navigating by the stars -- 4. Making our own stars: GPS -- 5. Navigation in airplanes -- 6. Navigation planning -- 7. A guide to further reading -- App. The navigational stars.
Includes bibliographical references (pages 253-256) and index.
Text in English.
Keywords: Navigation (Aeronautics) -- Mathematics; Navigation (Aeronautics) -- Mathematics